ANALISIS KETAHANAN PANGAN DAN KEMISKINAN RUMAHTANGGA TANI DI DESA TAWANGHARJO KECAMATAN GIRIWOYO KABUPATEN WONOGIRI - Dinna Dwi Tantias; Ken Suratiyah; Suhatmini Hardyastuti (Agro Ekonomi, 2010)
The purpose of this study was (1) determine the performance indicators of food security which includes food availability, food accessibility, food stability and food quality. (2) determine the level of farmer household food security. (3) knowing the farmer household expenditure. The study was conducted in Tawangharjo village, Giriwoyt, WOnogiri regency. Respondents are the farmer owners, tenants and sharecroppers who tilled the land area, a total of 30 (simple ransom smapling). Consumption of Household Food Security Rate Index (IKKPRT) to determine the level of farmer household food security. Food expenditure was measured by GSR (Good Service Ratio), poverty was measured by Sajogjo, ADB, FAO, and World Bank Criterion. The results shows that farmer household have sufficient food availability and stable, but the accessibility and level of nutritional adequacy is still relatively low.  IKKPRT value is81,56 in a state of sufficient food. Because the proportion of food expenditure' is greater than the non-food; it can be said to farmer household in poor condition and less prosperous.